2015
DOI: 10.11606/issn.1679-9836.v94i3p136-146
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve in elderly: neuropsychological aspects and the education role in the latest findings

Abstract: The elderly population is growing worldwide, and therefore cognitive decline and dementia is a major problem for healthcare system. However, many elders do not develop dementia or significant cognitive impairment even though present brain lesions, such as cortical atrophy and/or lesions, leading to the concept of Cognitive Reserve (CR). The main objective of this review is to establish the recent findings of CR in elderly cognition and explore some of the cognitive markers related to CR. In order to accomplish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(129 reference statements)
1
0
0
Order By: Relevance
“…Similar results has also been reported by Vuoksimaa et al (2013). Other studies also demonstrated that higher level of CR is directly associated with better performance in episodic memory (Dias et al, 2015;Fyffe et al, 2011;Opdebeeck et al, 2016).…”
Section: Introductionsupporting
confidence: 87%
“…Similar results has also been reported by Vuoksimaa et al (2013). Other studies also demonstrated that higher level of CR is directly associated with better performance in episodic memory (Dias et al, 2015;Fyffe et al, 2011;Opdebeeck et al, 2016).…”
Section: Introductionsupporting
confidence: 87%